2018
DOI: 10.1155/2018/4126245
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Enterocolitis in Moderate Preterm Infants

Abstract: Necrotizing enterocolitis (NEC) is a devastating morbidity usually seen in preterm infants, with extremely preterm neonates (EPT ≤28 weeks) considered at highest risk. Moderately preterm infants (MPT 28–34 weeks) constitute a large percentage of NICU admissions. In our retrospective data analysis of NEC in a single regional perinatal center, NEC was observed in 10% of extremely EPT and 7% of MPT, but only 0.7% of late-preterm/term admissions. There was an inverse relationship between postnatal age at onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
(32 reference statements)
1
17
1
Order By: Relevance
“…This was consistent with the findings of the United Kingdom study (7.5%) ( 16 ), and Polish (8.7%) ( 17 ). However, this finding was higher than the study conducted in multicenter Hospitals in China (2.4%) ( 13 ) and the United States (2.8%) ( 18 ). This could be because 61.2% of Ethiopian mothers think that pre-lacteal feeding is crucial for a child’s health and growth, the practice is as widespread there as it is in China and the United States ( 19 ); additionally, it may be also socio-economic, sample size, study area differences, and advanced neonatal and maternal care in China and the United States.…”
Section: Discussioncontrasting
confidence: 67%
“…This was consistent with the findings of the United Kingdom study (7.5%) ( 16 ), and Polish (8.7%) ( 17 ). However, this finding was higher than the study conducted in multicenter Hospitals in China (2.4%) ( 13 ) and the United States (2.8%) ( 18 ). This could be because 61.2% of Ethiopian mothers think that pre-lacteal feeding is crucial for a child’s health and growth, the practice is as widespread there as it is in China and the United States ( 19 ); additionally, it may be also socio-economic, sample size, study area differences, and advanced neonatal and maternal care in China and the United States.…”
Section: Discussioncontrasting
confidence: 67%
“…Another finding was the positive and significant correlation between disease stages and gestational age and birth weight. One study revealed that the incidence of NEC decreases with increasing gestational age 28 . Another study points out that NEC is more common in very low birth weight infants, which differs from the data found 29 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Other studies have used a variety of gestational age limits to define MPT, starting as low as 28 week gestation and up to 34 6/7 week infants. 11,[19][20][21] The lack of consensus definition of MPT limits our ability to make comparisons on a consistent maternal and infant population.…”
Section: Discussionmentioning
confidence: 99%